Pengaruh Budaya Organisasi Dan Komunikasi Internal Terhadap Kinerja Pegawai Pada Kantor Imigrasi Unit Layanan Paspor Wilayah I Pondok Pinang: The Influence of Organizational Culture and Internal Communication on Employee Performance at the Passport Service Unit of the Immigration Office Region I Pondok Pinang - Ikrar Ahmad; Rosmita Rosmita (CV Warnak Johanna Nusantara, 2025)
In the context of globalization and in terms of increasing community mobility, the role of immigration institutions is very important. This shows the urgency to see employee performance by understanding organizational culture and internal communication. The purpose of this study was to determine the effect of organizational culture and internal communication on employee performance. Data collection techniques used were observation, questionnaires and literature studies. This study was conducted on employees of the Immigration Office of the Passport Service Unit Region I Pondok Pinang using a quantitative descriptive method. The population of this study was 32 respondents and the sample used was the entire population, because it used a saturated sampling technique. The technique used in collecting data was by using a questionnaire distributed via a google form link. The results of the T-test study showed that there was a partial influence of organizational culture on employee performance with a t-count value of 3.983> 2.045, so Ho1 was rejected and Ha1 was accepted. There was a partial influence between internal communication on employee performance with a t-count value of 2.328> 2.045, so Ho2 was rejected and Ha2 was accepted. Meanwhile, the simultaneous influence between organizational culture and internal communication on employee performance with a calculated F value of 77.858 > 3.32 and a significance value of 0.000, Ho3 is rejected and Ha3 is accepted